miR-617 interacts with the promoter of DDX27 and positively regulates its expression: implications for cancer therapeutics - Sarkar, Neelanjana; Mishra, Radha; Gopal, Champaka; Kumar, Arun (Frontiers in Oncology, 2024)
Background Pervasive transcription of the eukaryotic genome generates noncoding RNAs (ncRNAs), which regulate messenger RNA (mRNA) stability and translation. MicroRNAs (miRNAs/miRs) represent a group of well-studied ncRNAs that maintain cellular homeostasis. Thus, any aberration in miRNA expression can cause diseases, including carcinogenesis. According to microRNA microarray analyses, intronic miR-617 is significantly downregulated in oral squamous cell carcinoma (OSCC) tissues compared to normal oral tissues. Methods The miR-617-mediated regulation of DDX27 is established by performing experiments on OSCC cell lines, patient samples, and xenograft nude mice model. Overexpression plasmid constructs, bisulphite sequencing PCR, bioinformatics analyses, RT-qPCR, Western blotting, dual-luciferase reporter assay, and cell-based assays are utilized to delineate the role of miR-617 in OSCC. Results The present study shows that miR-617 has an anti-proliferative role in OSCC cells and is partly downregulated in OSCC cells due to the hypermethylation of its independent promoter. Further, we demonstrate that miR-617 upregulates DDX27 gene by interacting with its promoter in a dose-dependent and sequence-specific manner, and this interaction is found to be biologically relevant in OSCC patient samples. Subsequently, we show that miR-617 regulates cell proliferation, apoptosis, and anchorage-independent growth of OSCC cells by modulating DDX27 levels. Besides, our study shows that miR-617 exerts its effects through the PI3K/AKT/MTOR pathway via regulating DDX27 levels. Furthermore, the OSCC xenograft study in nude mice shows the anti-tumorigenic potential of miR-617. Conclusion miR-617-mediated upregulation of DDX27 is a novel mechanism in OSCC and underscores the therapeutic potential of synthetic miR-617 mimics in cancer therapeutics. To the best of our knowledge, miR-617 is the 15th example of a miRNA that upregulates the expression of a protein-coding gene by interacting with its promoter.